KAJIAN HUKUM TERHADAP PERMOHONAN DISPENSASI KAWIN PADA PEREMPUAN DI BAWAH UMUR DI PENGADILAN AGAMA SEMARANG (Studi Kesehatan Reproduksi) - Munadhiroh Mudadhiroh (MIH Unsoed, 2016)
This study aimed to analyze the factors underlying the filing of application for a dispensation to marry the underage girls in Semarang Religion Court and analyze the legal considerations in Semarang Religion Court to request a dispensation to marry the underage girls in terms of aspect on reproductive health. This study using sociological juridical approach. Specification of research is analytic descriptive. There are four factors behind the filing of application for a dispensation to marry in the Religion Court of Semarang, which is already pregnant, religious and cultural factors, economic factors, and educational factors. Legal considerations of the judges in Religion Court of Semarang in setting request dispensation to marry not consider aspects of woman's reproductive health yet. The judges in Religion Court of Semarang in setting request dispensation to marry should consider womenâ€™s reproductive health aspects, age of marry should be upgrade based on womanâ€™s reproductive health age being 20 years old.Key words: the application, marriage dispensation, healthyÂ